2007
DOI: 10.1016/j.jacc.2007.03.058
|View full text |Cite
|
Sign up to set email alerts
|

Volume-to-Creatinine Clearance Ratio

Abstract: A V/CrCl ratio >3.7 was a significant and independent predictor of an early abnormal increase in serum creatinine after PCI in this unselected patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
2
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 342 publications
(76 citation statements)
references
References 33 publications
1
71
2
2
Order By: Relevance
“…The reported incidence of AKI is 1% to 3% in patients undergoing elective PCI17, 19, 20, 21 but rises significantly to 10% to 16% in patients undergoing pPCI 3, 22, 23. The large increase in incident AKI is the result of heart failure, hemodynamic instability, and pharmacological interventions associated with STEMI rather than the use of greater contrast volume.…”
Section: Discussionmentioning
confidence: 99%
“…The reported incidence of AKI is 1% to 3% in patients undergoing elective PCI17, 19, 20, 21 but rises significantly to 10% to 16% in patients undergoing pPCI 3, 22, 23. The large increase in incident AKI is the result of heart failure, hemodynamic instability, and pharmacological interventions associated with STEMI rather than the use of greater contrast volume.…”
Section: Discussionmentioning
confidence: 99%
“…Even small volumes (∼30 ml) of contrast medium can have adverse effects on renal function in patients at particularly high risk [54]. As a general rule, the volume of contrast received should not exceed twice the baseline level of eGFR in ml [55]. This means for patients with significant CKD reasonable goals would be: <30 ml for diagnostic cardiac catheterization and <100 ml for PCI, CT, and other intravascular studies.…”
Section: Differences In Iodinated Contrastmentioning
confidence: 99%
“…Recent studies investigating the predictive value of the CV/eClCr or CV/eGFR ratios for CI-AKI suggested that maximally acceptable CV should be individually calculated by multiplying the cutoff value of the ratio and each patient's eGFR [1,4,5,6]. The use of eGFR with BSA normalization can lead to an underestimation of the actual contrast removal rate in overweighed individuals and to an overestimation in underweighted ones [12], so the use of raw eGFR without BSA normalization rather than BSA-normalized eGFR is more appropriate when dealing with the toxicity of contrast medium.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that the ratio of contrast volume (CV) to either estimated glomerular filtration rate (eGFR) or creatinine clearance (eClCr) can be used as a single risk predictor for contrast-induced acute kidney injury (CI-AKI), since this ratio pharmacokinetically means the area under the curve (AUC) representing the systemic exposure of a contrast agent to the body [1,2]. When dealing with pharmacokinetic issues, it is more appropriate to use the raw eGFR in absolute numbers (ml/min) individualized with the removal of body surface area (BSA) normalization.…”
Section: Introductionmentioning
confidence: 99%